(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In recent years, the rapid growth in the use of digital technologies – particularly smartphones, tablets, and computers – has led to a significant increase in visual system load among children, adolescents, and adults. This literature review focuses on the analysis of the development and progression of visual disorders associated with prolonged use of digital devices, including Digital Eye Strain (DES), Computer Vision Syndrome (CVS), refractive errors, and myopia.